Testing and finite element analysis of reinforced concrete column footings failing by punching shear. (1st June 2015) - Vacev, Todor; Bonić, Zoran; Prolović, Verka; Davidović, Nebojša; Lukić, Dragan
Highlights: We analyzed behaviour of reinforced column footings laid on deformable subgrade. FEA and ANSYS software were successfully used as an analysis tool. Problem included nonlinearities, cracking and crushing, which impeded convergence. FEA solution of punching of column footings gave good results, close to field test. Improvement of the ANSYS concrete material model would be desirable and useful. Abstract: Finite element analysis (FEA) and engineering software is increasingly used in modelling of different structures and in analyzing their behaviour. The subject of this paper was an analysis of behaviour of reinforced concrete column footing laid on deformable subgrade and loaded by concentrated load until failure. The modelling and 3D nonlinear analysis were implemented by applying finite element method (FEM) and using software package ANSYS 14.5. Field test data were used for calibration of the FE model and validation of the adopted parameters for all materials. The comparison of the field test results and FEA results showed good agreement, but also revealed some questions regarding FEA, and especially concrete crushing.